2016
DOI: 10.1016/j.jocn.2015.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Thin-film optical notch filter spectacle coatings for the treatment of migraine and photophobia

Abstract: Previous evidence suggests optical treatments hold promise for treating migraine and photophobia. We designed an optical notch filter, centered at 480 nm to reduce direct stimulation of intrinsically photosensitive retinal ganglion cells. We used thin-film technology to integrate the filter into spectacle lenses. Our objective was to determine if an optical notch filter, designed to attenuate activity of intrinsically photosensitive retinal ganglion cells, could reduce headache impact in chronic migraine subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…Our finding is consistent with previous reports indicating that short-wavelength blue light generates more perceptual discomfort in comparison with long or medium wavelengths of light in visually normal 20,22,23 and clinical populations, 21 and correlates with the peak spectral sensitivity of melanopsin. 6 Our results are also consistent with studies that show alleviation of photophobia symptoms when patients with migraine 25 and benign essential blepharospasm 2,24 were fitted with tinted lenses that filter out blue light.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our finding is consistent with previous reports indicating that short-wavelength blue light generates more perceptual discomfort in comparison with long or medium wavelengths of light in visually normal 20,22,23 and clinical populations, 21 and correlates with the peak spectral sensitivity of melanopsin. 6 Our results are also consistent with studies that show alleviation of photophobia symptoms when patients with migraine 25 and benign essential blepharospasm 2,24 were fitted with tinted lenses that filter out blue light.…”
Section: Discussionsupporting
confidence: 89%
“…Third, short-wavelength blue light has been reported to induce the most visual discomfort, [20][21][22][23] whereas blue-filtering lenses have been reported to reduce the symptom in patients with photophobia. 2,24,25 Furthermore, the action spec-trum for visual discomfort and that for ipRGCs (~480 nm, blue light) 6,8 are remarkably similar. 23 Fourth, ipRGCs project directly to pain centers in the posterior thalamus where afferent retinal inputs converge with the trigeminal nociceptive pathway.…”
mentioning
confidence: 85%
“…In addition, filters manipulating short-wavelength light have been employed in the management of psychiatric and neurological (bipolar disorder, [38][39][40] depression, 32 ADHD, 41 blepharospasm, 42,43 migraine, [44][45][46] photosensitive epilepsy, 47 insomnia 32,41,48 ) and retinal conditions (rod monochromacy/achromatopsia, [49][50][51][52] retinitis pigmentosa, 53 others 54 ), as well as for reducing non-specific photophobia 46,55 and eye fatigue. 56,57 Coloured filters have also been used previously to improve reading difficulties and relieve visual stress 58,59 and symptoms of migraine, 60 though these are not specifically attenuating short-wavelength light 61 (but may do so, depending on the specific filter chosen).…”
Section: Introductionmentioning
confidence: 99%
“…24 We hope that future investigations of dry eye, visual quality of life, and migraine will help determine if dry eye treatments are helpful and if so, which treatments are most effective. Although photophobia and aura negatively affect visual quality of life, dry eye symptoms appear to be the strongest driver of poor visual quality of life.…”
Section: -Pearson's Correlation Coefficients and P Values For The 5 Smentioning
confidence: 99%
“…We also demonstrated that photophobia is correlated with headache impact, which lends support to our previous finding that treating photophobia can positively influence headache impact. 24 We hope that future investigations of dry eye, visual quality of life, and migraine will help determine if dry eye treatments are helpful and if so, which treatments are most effective.…”
Section: -Pearson's Correlation Coefficients and P Values For The 5 Smentioning
confidence: 99%